A new species of the South East Asian genus Sarax Simon, 1892 (Arachnida: Amblypygi: Charinidae) and synonymization of Sarax mediterraneus Delle Cave, 1986 - Seiter, Michael; Wolff, Jonas; Hörweg, Christoph (Zootaxa, 2015)
A new species of the whip spider genus Sarax Simon, 1892 from Cebu Island in the Philippines is described: Sarax huberi sp. nov. With the description of this species, the diversity of the genus is increased to three species in the Philippines. Some additional data on their natural environment and their specific habitat are presented and compared with sibling species. The synonymization of Sarax mediterraneus Delle Cave, 1986 with Sarax buxtoni (Gravely, 1915) is carried out.